The gender gap in peer-to-peer lending: Evidence from the People's Republic of China - Xiao Chen; Bihong Huang; Dezhu Ye (Asian Development Bank Institute (ADBI), 2019)
This paper documents and analyzes the gender gap in the online credit market. Using data from Renrendai, a leading peer-to-peer lending platform in the People's Republic of China (PRC), we show that lending to female borrowers is associated with better loan performance, including a lower probability of default, a higher expected profit, and a lower expected loss than for their male peers. However, despite the higher creditworthiness, we don't find any measurable gender impact on funding success rate, meaning that female borrowers have to compensate lenders by providing higher profitability to achieve a similar funding probability to their male peers. This evidence indicates the existence of a gender gap that discriminates against female borrowers. Further analysis implies that this gender gap is independent of the amount of information disclosed by borrowers.
Keywords: G21; J16; G20; 330; P2P lending; gender gap; loan performance